Revisiting ameloblastin; addressing the EMT-ECM axis above and beyond oral biology - Reseland, Janne E.; Heyward, Catherine A.; Samara, Athina (Frontiers in Cell and Developmental Biology, 2023)
Ameloblastin (AMBN) is best characterized for its role in dental enamel formation, regulating cell differentiation and mineralization, and cell matrix adhesion. However, AMBN has also been detected in mesenchymal stem cells in addition to bone, blood, and adipose tissue. Using immunofluorescence in a pilot scheme, we identified that AMBN is expressed in different parts of the gastrointestinal (GI) tract. AMBN mRNA and protein detection in several tissues along the length of the GI tract suggests a role for AMBN in the structure and tissue integrity of the extracellular matrix (ECM). Intracellular AMBN expression in subsets of cells indicates a potential alternative role in signaling processes. Of note, our previous functional AMBN promoter analyses had shown that it contains epithelial–mesenchymal transition (EMT) regulatory elements. ΑΜΒΝ is herein presented as a paradigm shift of the possible associations and the spatiotemporal regulation of the ECM regulating the EMT and vice versa, using the example of AMBN expression beyond oral biology.